(untitled) (International Journal of Engineering Management Science, 2022)
In this globalized world, it’s become more complex to manage logistics and supply chain. The nature of the business and the role of logistics & supply chain are not as same as now as before, this is due to digitalization, advancements in information & technology and changes in consumer buying behavior. The present study is descriptive in nature focusing on the role of supply chain management & logistics in new business models and studying the impact of technology in logistics sectors. Work load of logistics and supply chain management has increased from the emergence of online shops, as they extended their services at a wide range. They not only plan coordinate, warehouse and move the goods from point of origin to point of end-consumer but also helping the online shops to expand their business and increase their market share by attracting more customers through digital marketing, artificial intelligence.